Chemical and Structure Modification of Polymers 2015
DOI: 10.1201/b19300-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Pearlescent Biaxially Oriented Multilayer Polypropylene Film

Abstract: This study examines the literature of double-skin facade systems over the last decade, and, with the help of tables and graphics, investigates their advantages and disadvantages. Moreover, a detailed comparison is made between double skin façade systems. The results of the study show that the greatest advantage (95%) of double skin facade systems is their provision of natural ventilation. Other advantages are highlighted according to their percentage as follows: An increase in interaction between user and envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Thus, FTIR spectrum of Container 1 confirmed that it was mainly made of polypropylene. Additionally, the peaks at 1460 and 712 cm -1 indicated the existence of calcium carbonate (CaCO3) in container 1, because these peaks are the characteristic peaks of the CaCO3 [8].…”
Section: Functional Groups By Ftir Analysismentioning
confidence: 99%
“…Thus, FTIR spectrum of Container 1 confirmed that it was mainly made of polypropylene. Additionally, the peaks at 1460 and 712 cm -1 indicated the existence of calcium carbonate (CaCO3) in container 1, because these peaks are the characteristic peaks of the CaCO3 [8].…”
Section: Functional Groups By Ftir Analysismentioning
confidence: 99%
“…Binding of the HCl by an organotin mercaptide stabilizer 6 The induction period -the axial section on the time coordinate of the dehydrochlorination curveis a common criterion of all heat stabilizers. Normally, within this period, the processing takes place.…”
Section: The Mechanism Of Stabilizationmentioning
confidence: 99%
“…While control and 2.5% organotin stabilizer containing films are transparent, films with 5% organotin stabilizer are opaque white, indicating limited solubility of organotin stabilizer in PVC. 6…”
Section: Evaluating Stability Yellowness Index and Transparencymentioning
confidence: 99%
See 2 more Smart Citations